FIGURE 11 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 11. Measurements of Oxytoma octavia (d'Orbigny, 1850) (in mm). (A) Height to length. (B) Length of hinge line to length. (C) Length of the posterior part of the hinge line to total length of the hinge line. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 26, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112